Estymacja prawdopodobieństw przejścia między stanami zdrowia osóbw wieku 50 lat i więcej w Polsce w modelu wielostanowym - Łątkowski, Wojciech (Studia Demograficzne, 2015)
Poland will experience advanced population ageing driven by improvements in longevity, low fertility and retirement of baby boom cohorts. Given the higher morbidity prevalence observed at older ages, the demand for the elderly care is expected to increase. The study focuses on the dynamics of health of people aged 50 and over in Poland. We want to verify how the risks of the health status change are shaped over age and what the impact of sex is. The empirical analysis provides a description of a non-parametric multi-state model for transitions in health. The age- and sex-specific health transition rates and probabilities are estimated based on the European Union Statistics on Income and Living Conditions (EU-SILC) panel data for the years 2008–2011. The results confirm the well-known regularities in research on health: the risk of being unhealthy is increasing with age, while the probability of recovery is decreasing. Women have a higher risk of the onset of disability than men, whereas recovery to health is similar for men and women.